Theoretical and experimental studies on concerted elimination of 1, 2‐bromochloroethane monocation to C2H4+ and BrCl. Issue 2 (27th August 2020) - Wu, Hua; An, Mengdi; Wen, Junqing; Bai, Lihua; Li, Dongming; Liu, Jukun; Sun, Ruijuan; He, Wanlin; Lin, Lin; Li, Yumei
Abstract: Ab initio calculations for the concerted elimination of 1, 2‐bromochloroethane monocation (1, 2‐C2 H4 BrCl + ) to C2 H4 + and BrCl are performed using the Minnesota density functional M06‐2X and the def2‐TZVP basis set. Ab initio calculations are also carried out for the concerted elimination of 1, 2‐C2 H4 BrCl + to C2 H4 and BrCl + because the positive charge can be assigned to either moiety in the dissociative ionization process of 1, 2‐C2 H4 BrCl + . Our results demonstrate that the concerted elimination channel of 1, 2‐C2 H4 BrCl + to C2 H4 + and BrCl is preferred and that 1, 2‐C2 H4 BrCl + surpasses two energy barriers and then separates into C2 H4 + + BrCl through an asynchronous concerted process. Experimentally, we confirm that this elimination channel is from the dissociative ionization process of 1, 2‐C2 H4 BrCl + by using dc‐slice imaging technique. The time‐of‐flight mass spectra of 1, 2‐bromochloroethane induced by femtosecond laser pulses show that C2 H4 + occurs at a laser intensity of 6.0 × 10 13  W/cm 2, and BrCl + occurs at a higher laser intensity than C2 H4 + . This finding is consistent with the theoretical result that the appearance energy of C2 H4 + is lower than that of BrCl + . As such, the low‐velocity component of BrCl + is absent from our sliced images. Abstract : Pathways of 1, 2‐C2 H4 BrCl + to C2 H4 + and BrCl + were computed at the M06‐2X/def2‐TZVP level. Calculation results demonstrated that dissociation to C2 H4 + was preferred, and 1, 2‐C2 H4 BrCl + separated into C2 H4 + and BrCl by an asynchronous concerted mechanism. Experimentally, BrCl + occurred at a higher laser intensity than C2 H4 + in mass spectra, which was consistent with theoretical results. Eventually, the pathway of 1, 2‐C2 H4 BrCl + to C2 H4 + and BrCl was verified using the dc‐slice imaging technique.